Label-free impedimetric glycan biosensor for quantitative evaluation interactions between pathogenic bacteria and mannose - Cui, Feiyun; Xu, Yi; Wang, Renjie; Liu, Haitao; Chen, Li; Zhang, Qing; Mu, Xiaojing (Biosensors & bioelectronics, 2018)
In order to understanding the pathogenic mechanism of infectious diseases, it was important to study the selective recognition and interaction between pathogenic bacteria and host cells. In this paper, a novel electrochemical impedance biosensor was proposed, in which the Man/MUA-MH/Au sensing surface (Man: mannose; MUA: 11-mercapto eleven acid; MH: 6-mercapto hexanol) was fabricated and was of good biologically active and stability. The capture capacity of the designed sensing surface for S. typhimurium ATCC14028, E. coli JM109 and E. coli DH5α were characterized by Electrochemical impedance spectroscopy (EIS). According to Randless equivalent circuit and the Frumkin isotherm model, electron transfer impedance (Ret) was obtained and the binding affinity of the three bacteria and Man was calculated. It was shown that the sensing surface had a better binding affinity for S. typhimurium ATCC14028 with KADS(S.T.) = 2.16 × 106 CFU/mL. The impedance normalized value NIC (S.T.-Man) was of a good linear relationship with the logarithm of bacterial concentration (R2 = 0.96) in the range of 50–1000 CFU/mL. The detection limit was 50 CFU/mL. Meanwhile, the E. coli JM109 which expresses type 1 fimbriae was also adsorbed on the designed sensing surface with KADS(JM109) = 5.84 × 103 CFU/mL. It was illustrated that the novel electrochemical impedance biosensor could be more rapid and reliable for studying interactions between pathogen and glycan, and it was also perspective for a new point-of-care diagnostic tool for evaluating the pathogenicity bacteria. •A novel EIS biosensor was proposed for studying bacteria-glycan interactions.•A Man/MUA-MH/Au surface with good bioactivity and stability was constructed.•The adsorption coefficient of three kinds of bacteria were quantitatively detected.